Implementation of destination principle VAT on service exports in Indonesia: Analysis of PMK-32/PMK.010/2019 based on OECD guidelines - Hadwimantoro, Hadwimantoro (Educoretax, 2024)
Value Added Tax (VAT) is applied based on two fundamental concepts: the origin principle and the destination principle. Under the origin principle, taxes are levied where goods or services are produced, while under the destination principle, taxes are imposed where the goods or services are consumed. This research focuses on analyzing how the destination principle is implemented in the imposition of VAT on service exports, as governed by Regulation of the Minister of Finance No. 32/PMK.010/2019 regarding the limitations on taxable activities and types of services whose exports are subject to VAT. The OECD International VAT/GST Guidelines are used as a reference in this analysis to reduce distortions in international trade and minimize the risk of differences in tax collection principles between countries. The results of the study show that PMK-32/PMK.010/2019 has implemented the destination principle in accordance with the OECD guidelines, but there are still several challenges in its implementation, especially in ensuring tax neutrality and legal clarity in cross-border transactions. This study provides important insights for policymakers in improving tax regulations to support sustainable and equitable economic growth.